Assessing the destructive behaviors of two white-rot fungi on beech wood - Bari, Ehsan; Taghiyari, Hamid Reza; Naji, Hamid Reza; Schmidt, Olaf; Ohno, Katie M.; Clausen, Carol A.; Bakar, Edi Suhaimi (Elsevier, 2016)
This research assessed the destructive behaviors of two white-rot fungi, Pleurotus ostreatus and Trametes versicolor and compared their degradation capabilities on solid oriental beech wood (Fagus orientalis Lipsky). Beech wood specimens were exposed to both fungi for a period of 120 days based on the specifications in the EN-113 standard. Mechanical properties and chemical composition of the specimens were measured every 15 days. Mass loss (ML) caused by the two fungi were not significantly different at the last stage of exposure, although T. versicolor showed higher ML at the middle exposure intervals. Compression strength parallel to grain, hardness, and impact bending values were higher in specimens exposed to P. ostreatus, although differences were not statistically significant. Microscopic images showed nearly the same decay patterns for both fungi. The results of the chemical assessment indicated that degradation of cell wall components was approximately the same for both fungi, but in some case T. versicolor showed a slightly higher potential to decay compared to P. ostreatus, especially in the early stages of exposure. The two fungi differed in their ability to reduce degree of polymerization (DP) holocellulose of beech wood. It was concluded that the destructive behaviors ability of both fungi was considerable.